Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/bi9916325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peroxisomal 3-Hydroxy-3-methylglutaryl Coenzyme A Reductase in UT2* Cells:  Sterol Biosynthesis, Phosphorylation, Degradation, and Statin Inhibition

Abstract: We have previously identified a CHO cell line (UT2 cells) that expresses only one 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase protein which is localized exclusively in peroxisomes [Engfelt, H.W., Shackelford, J.E., Aboushadi, N., Jessani, N., Masuda, K., Paton, V.G., Keller, G.A., and Krisans, S.K. (1997) J. Biol. Chem. 272, 24579-24587]. In this study, we utilized the UT2 cells to determine the properties of the peroxisomal reductase independent of the endoplasmic reticulum (ER) HMG-CoA reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…33 Despite these mutations, the UT2* cell line expresses a smaller but enzymatically active isoform of HMGCR that has lower specific activity (52 versus 275 pmol·min Ϫ1 ·mg Ϫ1 ) and statin sensitivity compared with the normal isoform. 34 The authors were unable to identify an HMGCR transcript that could account for this novel isoform; however, this finding suggests that splicing mutations around exon 13 can result in an active, and partially statin-resistant, isoform.…”
Section: Discussionmentioning
confidence: 95%
“…33 Despite these mutations, the UT2* cell line expresses a smaller but enzymatically active isoform of HMGCR that has lower specific activity (52 versus 275 pmol·min Ϫ1 ·mg Ϫ1 ) and statin sensitivity compared with the normal isoform. 34 The authors were unable to identify an HMGCR transcript that could account for this novel isoform; however, this finding suggests that splicing mutations around exon 13 can result in an active, and partially statin-resistant, isoform.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Engfelt et al (16) identified the responsible mutations in the structural gene for reductase. By growing UT-2 cells in the absence of mevalonate, they have established a new cell line, designated as UT-2* cells, and demonstrated that UT-2* cells had up-regulated HMGCoA reductase activity, which was localized exclusively to peroxisomes and the peroxisomal enzyme in these cells was sufficient for survival without mevalonate (15,17). Based on the detailed characterization of UT-2* cells, they suggested the existence of a second, peroxisome-specific gene for the reductase.…”
Section: Discussionmentioning
confidence: 99%
“…Given the major role of HMG-CoA reductase in the mevalonate pathway, it is tempting to hypothesize that mammalian cells also have a second gene for the enzyme. In fact, although the classic form of the enzyme is a transmembrane protein anchored to the endoplasmic reticulum (ER), recent studies using a mutant cell line that lacks the ER isoform of the enzyme indicate the existence of a second isoform of the reductase exclusively localized in peroxisomes and that the peroxisomal activity might be due to a second gene (15)(16)(17).…”
Section: -3)mentioning
confidence: 99%
“…The activity in peroxisomes was less than 5% of the total HMGCR in the cell under control conditions, but reached up to 30% after treatment with cholestyramine (11). The presence of significant amounts of peroxisomal HMGCR has been confirmed by other groups (12,13) and in other tissues and organisms [hamster ovarian epithelium (CHO cells) (14)(15)(16); rat brain (17)]. …”
Section: Subcellular Distribution Of Classical Hmg-coa Reductasementioning
confidence: 79%
“…How does mevalonate withdrawal cause a stable [inheritable? see (16)] change in HMGCR expression? Do the cloned transcripts really represent the complete diversity of existing transcripts, given that so many different splice variants are observed in UT2* cells, although the mutations are localized and well defined?…”
Section: Subcellular Distribution Of Classical Hmg-coa Reductasementioning
confidence: 99%